Handout Bioteknologi SMK “Pemanfaatan Dami Nangka sebagai Bahan Dasar Pembuatan Nata” Meningkatkan Kemampuan Berpikir Kreatif Siswa - Galina Istiqhfarini; Utami Sri Hastuti; Dwi Listyorini (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Learning is expected to provide learning experiences to students in order to understand learning material. The contextuality of learning resources and learning media must be improved. Biotechnology Handout